Pengaruh Variabel Fundamental pada Harga Saham Bank yang Terdaftar di Bursa Efek Indonesia Sebelum dan pada Masa Krisis Ekonomi Global - Ernawati -; Fifi Swandari (Jurnal Aplikasi Manajemen, 2012)
The aims of this research are to analyze the impact of fundamental variables on bank stock price in two different period. We analyze two years before and one year during global economic crisis in Indonesian Stock Market. The samples consist of 24 banks listed at Indonesia Stock Market. Linier regression is used to analyzed the impact of independent variables on dependent variable. We use Capital Adequate Ratio (CAR), Non Performing Loan ( NPL), Return on Asset (ROA), ratio Operating Cost to Operating Revenue (BOPO), Loan to Deposit Ratio (LDR) and deposit rate as independent variables. Dependent variable is banks stock price. We find all fundamental variables and deposit rate have impact on banks stock price simultaneosly before crisis period. Different result showed in another period, none of the variables have impact on banks stock price. We find ROA and LDR have impact on bank stock price partially before crisis. CAR, NPL, BOPO and deposit rate have no impact on banks stock price. This result shows that fundamental variables have different impact in two different period. The potential explanation is investors become irrational in the period of crisis so none of fundamentals variables have no impact on banks stock price.Keywords: fundamentals variables, bank stock price, global economic crisis period.